Strategi Unit Pelayanan Teknis Perlindungan Perempuan dan Anak (UPT PPA) Yogyakarta dengan Stakeholder dalam Menangani Kasus Kekerasan dalam Rumah Tangga - Pertiwi, Garnis Fibria Dian; Saptatiningsih, Rosalia Indriyati (Jurnal Kajian Gender dan Anak, 2023)
Abstract This research aims to analyze the handling strategies of Domestic Violence Cases by the Women and Children Protection Technical Service Unit in the city of Yogyakarta. The method used is a qualitative research method based on the phenomenology paradigm, while data collection is done through observation, interviews, and documentation. The conclusion of this research is that the Women and Children Protection Technical Service Unit in Yogyakarta collaborates and synergizes with various stakeholders, including the Department of Women Empowerment and Child Protection, Population and Family Planning Control Agency (DP3AP2KB), Ministry of Women